2020
DOI: 10.1002/cjoc.202000368
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aerobic Oxidative Ring Expansion of Isatins: A Facile Entry to Isoquinolino‐Fused Quinazolinones

Abstract: A copper-catalyzed aerobic oxidative ring expansion reaction of isatins with 1,2,3,4-tetrahydroisoquinoline for the synthesis of tetracyclic quinazolinones has been developed. This reaction is performed smoothly under simple conditions to give the corresponding products in moderate to good yields with good functional group tolerance. The capacity of the resultant 5H-isoquinolino[1,2-b]quinazolin-8(6H)-one for a range of palladium-catalyzed directing C-H activation has been further demonstrated, thus giving a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Based on control experiments and previous studies, 22–24,42–44 a possible reaction mechanism was proposed (Scheme 5). The mechanism involves two reaction pathways: first, tetrahydroisoquinoline 3a undergoes oxidative dehydrogenation to 3,4-dihydroisoquinoline 6 under visible light irradiation in the presence of 9-fluorenone /O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on control experiments and previous studies, 22–24,42–44 a possible reaction mechanism was proposed (Scheme 5). The mechanism involves two reaction pathways: first, tetrahydroisoquinoline 3a undergoes oxidative dehydrogenation to 3,4-dihydroisoquinoline 6 under visible light irradiation in the presence of 9-fluorenone /O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] Traditional synthetic methods for fused quinazolinones involve the oxidative decarboxylation of isatin and tetrahydroisoquinoline (Scheme 2a and b). 22,23 Furthermore, they can be obtained by copper or cobalt-catalyzed C(sp 2 )-H amination and cyclization of 2-aminoarylmethanols with isoquinolines or pyridines (Scheme 2c). 24,25 Secondary amines undergo redox neutral reactions with aminobenzaldehyde under conventional and microwave heating to provide polycyclic amines via α-amination/N-alkylation of amines as precursors to various quinazolinone alkaloids and their analogues (Scheme 2d).…”
Section: Introductionmentioning
confidence: 99%
“…Deng and co-workers developed a copper( ii )-catalyzed aerobic oxidative ring-opening reaction of isatins 38 with tetrahydroisoquinolines 39 for the synthesis of tetracyclic quinazolinones 40 (Scheme 21). 29 The optimal conditions showed that Cu(OTf) 2 (15 mol%) can smoothly catalyze the intermolecular aerobic oxidative ring-opening reaction in DMSO at 130 °C in the presence of O 2 , affording tetracyclic quinazolinones 40 in high yields. Various electron-donating and electron-withdrawing groups of the aryl rings were well tolerated and there was no straightforward correlation between the electronic properties of the substituents and the reaction efficiency.…”
Section: Ring-opening Strategy To Prepare 23-fused Quinazolinonesmentioning
confidence: 99%
“…Because of their ubiquity and broad biological properties, construction of such heterocyclic frameworks has received considerable attention from organic and medicinal chemists. Classic approaches to the synthesis of these compounds include oxidative decarboxylative cyclization of isatins or isatoic anhydrides with dihydro- or tetrahydroisoquinolines , (Scheme a) and cyclization of anthranils or 2-nitro/2-amino benzyl alcohols with tetrahydroisoquinolines (Scheme b) . These compounds can also be synthesized by photoredox-catalyzed intramolecular radical cyanide insertion (Scheme c) or Lewis-acid-catalyzed annulation using triethoxymethane (HC­(OEt) 3 ) (Scheme d). , In recent years, significant progress has been made in the synthesis of quinazolinone-fused polycyclic compounds by C–H amination reactions of substrates bearing azide, nitro, amino, , or amide groups serving as the nitrogen source (Scheme e).…”
Section: Introductionmentioning
confidence: 99%